2022
DOI: 10.1186/s12891-022-05207-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pain on quality of life in patients with osteoarthritis: a cross-sectional study from Palestine

Abstract: Background Osteoarthritis is one of the most common musculoskeletal problems. Pain is the most common complaint and the most significant cause of decreased health-related quality of life (HRQOL) among osteoarthritic patients. The objectives of this study were to assess the impact of pain on quality of life among patients with osteoarthritis and to assess the association of sociodemographic and clinical factors with HRQOL. Methods Using a cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 44 publications
(45 reference statements)
2
14
0
2
Order By: Relevance
“…Each of them received a score ranging from 0 to 10, and a pain interference score was calculated by summing up the marks earned on the seven questions, the resultant score was between 0 and 70 [ 22 ]. Patients with a total 10-point score of ≤ 5 were considered ‘low interference’, while those who have a score of > 5 were marked as ‘high interference’ [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of them received a score ranging from 0 to 10, and a pain interference score was calculated by summing up the marks earned on the seven questions, the resultant score was between 0 and 70 [ 22 ]. Patients with a total 10-point score of ≤ 5 were considered ‘low interference’, while those who have a score of > 5 were marked as ‘high interference’ [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, the total score ranges between 0 and 40, which was converted into a 10-point scale. A score of ≤ 4 was considered mild, > 4–6 was moderate, and > 6 was severe [ 24 ]. In addition, a picture of the human body is shown, which allows the patient to point to pain sites that he complains of.…”
Section: Methodsmentioning
confidence: 99%
“…One study's results indicated that psychological factors are strongly related to pain level 16 . Pain contributes to functional limitations and reduced QoL 17 . Physical function, bodily pain, and mental health are strongly associated with functional independence 18 …”
Section: Introductionmentioning
confidence: 99%
“…16 Pain contributes to functional limitations and reduced QoL. 17 Physical function, bodily pain, and mental health are strongly associated with functional independence. 18 Also, it is reported that women and older people, people with less than 12 years of education, those out of work, and those overweight have potentially higher prevalence of OA.…”
mentioning
confidence: 99%
See 1 more Smart Citation